2010
DOI: 10.1158/1078-0432.ccr-09-1758
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Human Renal Cell Carcinoma by Adoptive Transfer of Autologous Transforming Growth Factor β–Insensitive CD8+ T Cells

Abstract: Purpose: Transforming growth factor-β (TGF-β) is a potent immunosuppressor that has been associated with tumor evasion from the host immune surveillance and, thus, tumor progression. We tested a novel immunotherapy for human renal cell cancer (RCC) using a technique that involves the adoptive transfer of autologous tumor-reactive, TGF-β-insensitive CD8 + T cells into human RCC-challenged immunodeficient mice to identify its potent antitumor responses.Experimental Design: The present study was conducted using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…TGFβ also directly affects CD8 + cytotoxic T lymphocytes (CTLs). In vivo experiments have also demonstrated that such lymphocytes with truncated TGFβ signals mount a robust anti-tumor immune response (13-16). Additionally, TGFβ suppresses CTL activity and differentiation, through repression of several genes involved in an anti-tumor immune response including GranzymeB (17), an anti-tumor serine protease found in CTL-associated cytotoxic granules (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…TGFβ also directly affects CD8 + cytotoxic T lymphocytes (CTLs). In vivo experiments have also demonstrated that such lymphocytes with truncated TGFβ signals mount a robust anti-tumor immune response (13-16). Additionally, TGFβ suppresses CTL activity and differentiation, through repression of several genes involved in an anti-tumor immune response including GranzymeB (17), an anti-tumor serine protease found in CTL-associated cytotoxic granules (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…A second cause appears to be the rapid loss of secretory and cytolytic function of the TILs induced by factors within the tumor microenvironment (such as transforming growth factor (TGF) β) and by the upregulation of intrinsic negative regulators (such as PD1 and diacylglycerol kinase (DGK) (14, 35), a phenomenon also documented in endogenous TILs (4, 5). Attempts to overcome these limitations include introducing chemokine receptors into CAR cells (39), reducing expression levels of DGK (35), or by using dominant negative TGFβ receptors to prevent TGFβ-mediated inactivation of cytotoxic T lymphocytes in the tumor microenvironment (TME) (40-42). …”
Section: Discussionmentioning
confidence: 99%
“…TGF- β is a potent immunodepressant and blocking of TGF- β effects on T cells can improve antitumor efficacy of T cells after ACT for malignancies [153, 154, 201]. Administration of TGF- β receptor I kinase inhibitor increases tumor infiltration by NK, T cells and macrophage and increases survival in glioma-bearing mice [202, 203].…”
Section: Modification Of the Host Environmentmentioning
confidence: 99%